Society for Cardiovascular Magnetic Resonance reference values (“normal values”) in cardiovascular magnetic resonance: 2025 update - Kawel-Boehm, Nadine; Hetzel, Scott J.; Ambale-Venkatesh, Bharath; Captur, Gabriella; Chin, Calvin W.L.; François, Christopher J.; Jerosch-Herold, Michael; Luu, Judy M.; Raisi-Estabragh, Zahra; Starekova, Jitka; Taylor, Michael; van Hout, Max; et al. (Journal of cardiovascular magnetic resonance, 2025)
Quantitative assessment of morphological and functional cardiac parameters by cardiovascular magnetic resonance (CMR) is essential for research and routine clinical practice. Beyond established parameters of chamber size and function, tissue properties such as relaxation times play an increasing role. Normal reference ranges are required for interpretation of results obtained by quantitative CMR. Since the last publication of the “normal values review” in 2020 many new publications related to CMR reference values have been published, which were integrated in this update. The larger sample size provides greater statistical confidence in the estimates of upper and lower limits, and enables further partitioning, e.g., by age and ethnicity for several parameters. Previous topics were expanded by new sections. [Display omitted]